Don´t Ask Me Who I Want to Stay": The Voice of Children and Grandparents in Application Judicial Guard - Cardoso, Vanessa Silva; Costa, Liana Fortunato (Revista de Psicologia da IMED, 2014)
This article discusses the participation of children during legal proceedings involving grandparents and children in the child custody situation of these infants. This is a qualitative research that was conducted during the psychosocial care in a District Family Court of a Court of Justice. The research attempted to listen and understand the anxieties and fears of these children since they are developing beings that need to be protected. The results pointed to the knowledge of the perceptions of the child that there is a dispute in which she feels the loss and asks for the professionals not to take any position. What should not be confused is the fact of giving word to children in order to decide who she will stay with.